1986
DOI: 10.1139/v86-254
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectroscopic studies of solvent effects on the conformation of n-alkanes

Abstract: . Can. J. Chem. 64, 1544Chem. 64, (1986. The infrared spectra of specifically deuterated n-tridecane-7,7-d2 pure and mixed with several linear and branched hydrocarbons have been measured as a function of temperature. ' The average gauche fraction at the middle of the n-tridecane chain has been determined from the intensities of conformation-specific CD2 rocking bands. The results indicate that the concentration of gauche rotarners in the centre of the n-CI3 chains varies with the solvent. For example, when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The ν s (CH 2 ) peak frequency is a popular indicator of order not only in bulk alkane systems but also in surface-bound alkane systems as probed by surface vibrational methods such as surface FTIR and vibrational sum-frequency generation. , This indicator should be used with some caution, however, in light of the fact that the ν s (CH 2 ) frequency shifts by 6−8 cm -1 for neat octadecane in the crystalline state. This shift is a clear indication that this indicator alone does not adequately describe the conformational state of these systems.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The ν s (CH 2 ) peak frequency is a popular indicator of order not only in bulk alkane systems but also in surface-bound alkane systems as probed by surface vibrational methods such as surface FTIR and vibrational sum-frequency generation. , This indicator should be used with some caution, however, in light of the fact that the ν s (CH 2 ) frequency shifts by 6−8 cm -1 for neat octadecane in the crystalline state. This shift is a clear indication that this indicator alone does not adequately describe the conformational state of these systems.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, the IR spectra of alkanes also contain modes that are sensitive to alkane conformational order. Specifically, those modes cited most frequently as containing information about conformational order include the ν s (CH 2 ) and ν a (CH 2 ) peak frequencies (∼2850 and ∼2922 cm -1 ) and the ν(C−C) gauche, trans, and kink modes (∼1000−1300 and ∼620−700 cm -1 ). These indicators are important in elucidating alkane structure in materials; however, the chain coupling information and numbers of gauche and trans conformers provided by these indicators are only a small portion of the information necessary for a complete molecular understanding of the disorder in these materials. More direct comparison between Raman and IR spectral data for elucidation of conformational order is difficult, because the majority of intense Raman-active modes are either weak in the IR or IR-inactive and vice versa .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An electron diffraction study of the alkanes n -butane through n -heptane by Bartell and Kohl 4 revealed that the gas-phase conformations often contain gauche dihedral angles, with relatively high populations of conformers with single gauche bonds for n -pentane, n -hexane, and n -heptane. IR measurements for deuterated n -tridecane were interpreted to indicate significant alteration of gauche populations in different alkane solvents . However, Menger and D'Angelo 6 used 13 C NMR to observe the conformational equilibria of undecane-2,5-di- 13 C in solvents ranging from chloroform to aqueous ethanol; by measuring 3 J CC , they obtained the fraction of trans and gauche for the C3−C4 bond.…”
Section: Introductionmentioning
confidence: 99%